2021
DOI: 10.1590/1678-4685-gmb-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

An immunogenetic view of COVID-19

Abstract: Meeting the challenges brought by the COVID-19 pandemic requires an interdisciplinary approach. In this context, integrating knowledge of immune function with an understanding of how genetic variation influences the nature of immunity is a key challenge. Immunogenetics can help explain the heterogeneity of susceptibility and protection to the viral infection and disease progression. Here, we review the knowledge developed so far, discussing fundamental genes for triggering the innate and adaptive immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 292 publications
(363 reference statements)
0
3
0
Order By: Relevance
“…This tool may help leverage SNP data to gain power in HLA association studies. The CHIC also produced a broad review on immunogenetic parameters (e.g., HLA, KIR, complement, cytokines and chemokines receptors) and their role in COVID-19 ( Aguiar et al, 2021 ). A more specific review of COVID-19 and HLA associations ( Douillard et al, 2021 ) highlights links between the pathology and HLA at different levels, from allele frequency correlation to HLA associations and haplotypes.…”
Section: Introduction To Human Leukocyte Antigens: Creating Immunity From Diversitymentioning
confidence: 99%
“…This tool may help leverage SNP data to gain power in HLA association studies. The CHIC also produced a broad review on immunogenetic parameters (e.g., HLA, KIR, complement, cytokines and chemokines receptors) and their role in COVID-19 ( Aguiar et al, 2021 ). A more specific review of COVID-19 and HLA associations ( Douillard et al, 2021 ) highlights links between the pathology and HLA at different levels, from allele frequency correlation to HLA associations and haplotypes.…”
Section: Introduction To Human Leukocyte Antigens: Creating Immunity From Diversitymentioning
confidence: 99%
“…Furthermore, the HLA alleles that each of these centenarians carry were described, being likely candidates to influence infection outcomes [68][69][70] and longevity [71]. Many studies have reported potential HLA alleles implicated in response to SARS-CoV-2 infection [72], whether they were identified in a specific geographic region or globally. This influence is suggestively related to differential antigen presentation and interaction with the T cell receptor [73].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that SNP rs9277534 regulated the expression of HLA-DP antigens affecting several important physiological and pathological pathways [18] , [19] . Spontaneous recovery from Hepatitis A virus infection in Asian and European individuals carrying the rs9277534A variant has previously been reported [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%